Extrospection: Zen and the art of being posthuman in Ruth Ozeki's A Tale for the Time Being. Issue 10 (3rd October 2022) - Fernandez, Leslie J.
ABSTRACT: The rapid development of the field of Posthumanism is testament to the field's importance for contemplating the crucial questions of how we might overcome the various shortcomings of humanism. Yet, despite its productive insights and sharp anti-humanist critique there remains the question of translating these into a praxis. I argue that a critical posthumanist praxis remains an underexplored aspect of the field and I explore productive sites of engagement from which post humanism may begin to explicate a suitable praxis. For this, I turn to Ruth Ozeki's novel, A Tale for the Time Being, a text which is deeply invested in posthumanist problematics, but also juxtaposes this with an extended meditation on Zen Buddhist philosophy. Ozeki's book thus offers a productive site upon which to stage an encounter between posthumanism and Zen Buddhism. I argue that reading the novel's Zen themes alongside posthumanist theory offers productive ways of developing a posthumanist praxis. Specifically, I explore what I term as extrospection, an analogous practice to introspection that differs through its deconstruction of subject-object binaries. Additionally, I argue that the novel reframes our ethical and political frameworks away from ontology, and towards modes of relationality through its exploration of the 'time-being.'